Carbon and nitrogen contents in particle–size fractions of topsoil along a 3000 km aridity gradient in grasslands of northern China - X.-G. Wang; S. A. Sistla; X.-B. Wang; X.-T. Lü; X.-G. Han (Biogeosciences, 2016)
Climate factors such as aridity significantly influence soil carbon (C) and nitrogen (N) stocks in terrestrial ecosystems. Further, soil texture plays an important role in driving changes of soil C and N contents at regional scale. However, it remains uncertain whether such changes resulted from the variation of different soil particle–size factions and/or the C and N concentrations in those fractions. We examined the distribution of total C and N in both bulk soil and different soil particle–size fractions, including sand (53–2000 µm), silt (2–53 µm), and clay (< 2 µm), along a 3000 km transect in arid and semi-arid grasslands of northern China. Across the whole transect, sand content was positively and silt content was negatively correlated with increasing aridity. Carbon content in bulk soils (0–10 cm) ranged from 4.36 to 46.16 Mg C ha−1, while N content ranged from 0.22 to 4.28 Mg N ha−1 across different sampling sites on the transect. The total C and N concentrations and contents in bulk soils as well as in the three particle–size fractions tended to be negatively correlated with aridity. The concentrations and contents of total C and N in bulk soils were positively correlated with silt and clay contents and negatively correlated with sand content. Positive correlations were observed between the concentrations and contents of C or N in bulk soils and the C or N concentrations in the three soil particle–size fractions. By characterizing such a large scale aridity gradient, our results highlight that aridity would decrease soil C and N contents both by favoring increased sand content and by decreasing C and N concentrations in all the three soil fractions. These patterns thus have significant implications for understanding soil C and N sequestration under scenarios of increasing aridity in global drylands that are predicted to occur this century.